The influence of welding parameters and corrosive environment on the joint strength of resistance spot-welded mild steel sheets - Ahmad Azid Tahar Ahmad Latiffi
This final year peoject is carried out to study the influence of welding parameters (welding current and welding cycle) on the joint strength of resistant spot-welded mild steel sheets in ambient and corrosive environment. The relationship of the tensile strength, microhardness and nugget area of spot welded mild steel sheets are the main concerns in this study.